Field Performance Evaluation of Tractor Drawn Tillage Implement Used in Hilly Regions of Arunachal Pradesh - Singh, M. U. (Indian Journal of Hill Farming, 2018)
Selecting a most energy efficient tillage system often require the field performance data of various tillage implements under varying local conditions. Unfortunately the performance and energy input data for many of these tillage implements are very rear and not readily available in the hill regions of Arunachal Pradesh. Such information will probably guide the farmers of these regions in selection of suitable tillage implements. Keeping the importance of such information in mind, the present study was conducted to determine the field performance of tractor drawn tillage implements namely 2-bottom mouldboard plough, 2-bottom disk plough and spring loaded 7-tine cultivator. The percentages of width actually utilized (average effective width) were measured to be 86.67 % (52 cm), 84.7 % (59.3 cm) and 61.21 % (101 cm) for mouldboard plough, disk plough and tine cultivator respectively. Among the implements the spring loaded tine cultivator recorded the minimum draft per unit width (3.34 kNm-1) and power (3.29 kW) followed by disk plough (9.01 kNm-1) & (5.03 kW) and mouldboard plough (11.69 kNm-1) & (7.2 kW). The spring tine cultivator also recorded the highest average field capacity (0.22 ha/h) and lowest fuel consumption of 18.13 L/ ha (4.01L/h). The average effective field capacity and fuel consumption of mouldboard plough and disk plough were respectively 0.168 ha/h & 26.87L/ha (4.48 L/h) and (0.16 ha/h) & 24.79 L/ha (3.95 L/h). However, the maximum field efficiency was observed in disk plough (83.75 %), followed by mouldboard plough (78.75 %) and spring tine cultivator (64.1%). The minimum delay time (time lost) per hectare was obtained with used of disk plough (1.16 h/ha), followed by mouldboard plough (1.28 h/ha) and spring tine cultivator (1.63 h/ha).